RISK FACTORS FOR MORTALITY IN PEDIATRIC TRAUMATIC BRAIN INJURY IN THE PEDIATRIC INTENSIVE CARE UNIT (PICU) OF RSUD DR. MOEWARDI - Rusyda, Ayusya Khairunnisa; Sri Martuti; Aisya Fikritama Aditya (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Traumatic brain injury (TBI) represents the most common type of injury globally and can lead to death or permanent disability in children. In Indonesia, most existing studies have concentrated on adult TBI cases. This study aimed to identify the risk factors associated with mortality in pediatric patients with traumatic brain injury. This research employed an analytical observational approach with a cross-sectional design. Data were obtained from the medical records of pediatric patients aged 1–18 years diagnosed with TBI and admitted to the PICU of RSUD Dr. Moewardi between January and December 2023. A total of 40 patients were included. Statistical analyses were conducted using the Chi-square or Fisher's Exact test and logistic regression via SPSS. Mortality occurred in 25% of the patients (10 out of 40). Bivariate analysis indicated that a Glasgow Coma Scale (GCS) score ≤8 (OR = 36; 95% CI = 3.79–342.02; p < 0.001) and abnormal pupillary response (OR = 7.99; 95% CI = 2.73–84.18; p = 0.047) were significantly associated with mortality. Multivariate analysis identified a GCS score ≤8 as the most significant risk factor (OR = 22.87; 95% CI = 2.15–243.20; p = 0.009), followed by abnormal pupillary response (OR = 7.99; 95% CI = 2.73–84.18; p = 0.047). In conclusion, a GCS score ≤8 and abnormal pupillary response are significant risk factors for mortality in pediatric TBI patients admitted to the PICU of RSUD Dr. Moewardi.